Draining New Orleans : The 300-Year Quest to Dewater the Crescent City - Campanella, Richard (Book collections on Project MUSE., 2023)
"Draining New Orleans is the first full-length book entirely devoted to one of the world's most challenging drainage problems: the reclamation and drainage of a fluvial delta for the development of the City of New Orleans. Renowned Crescent City geographer and historian Richard Campanella introduces readers to the epic challenges and ingenious efforts to dewater New Orleans. With forays into geography, public health, engineering, architecture, politics, sociology, race relations, and disaster response, he recovers the herculean effort to 'reclaim' the city's swamps and marshes and install subsurface drainage for urbanization. This is not a story about mud; rather, it is a history of people, power, and the making of place. Campanella emphasizes the role of empowered, colorful individuals who spearheaded efforts to separate water from dirt and create value in the process not only for the community, but also for themselves. Campanella opens with a festive scene on Mardi Gras weekend 1915, in which an elaborate parade for 'the Drainage King'--a local hero by the serendipitous name of George Hero--brought an elite entourage to the edge of the Barataria swamp to witness the activation of gigantic pumps, via a telephonic connection to President Woodrow Wilson in the White House. What transpired in the years and decades ahead can only be understood by going back two centuries-to the geological formation and indigenous occupation of this delta and continuing through the colonial, antebellum, postbellum, and Progressive eras to modern times. The consequences of the dewatering of New Orleans are both triumphant and tragic. The city's engineering prowess made it a world leader in drainage technology, yet also a vulnerable victim of its own success. And by no means is the story over, for amid the uncertainty wrought by soil subsidence, coastal erosion, and climate change, the next generation of drainage experts are striving to improve on the past by doing something utterly inconceivable to their predecessors: rewatering New Orleans"--